Comparative analysis of the effectiveness of quadratus lumborum and transversus abdominis muscle blocks for postoperative pain relief during laparoscopic robot-assisted total hysterectomy. - Dossov, Mukhit; Babashev, Baurzhan; Ualiyev, Dastan; Seitenov, Serik; Zhailauova, Azhar; Bikibaev, Sayat (Pain medicine, 2024)
The purpose of this study was to compare and evaluate the analgesic effectiveness of quadratus lumborum block (QLB) and transversus abdominis plane bloc block (TAPB) after laparoscopic robot-assisted total hysterectomy. Materials and methods. A prospective study of female patients (n=101), with physical status ASA I-II, who underwent laparoscopic robot-assisted total hysterectomy under multicomponent general anesthesia. In random order, patients were randomized into three groups: the first group (CON, n=40) - control, where no blocks were performed, the second group (TAPB, n=30) - a blockade of the transverse abdominis muscle, the third group (QLB, n= 31) – blockade of the quadratus lumborum muscle was performed. After surgery, pain was assessed using a 10-point digital visual analogue scale, and postoperative nausea and vomiting were assessed. (PONV) Average arterial pressure and heart rate were recorded. Additionally, the next morning, a survey was conducted to assess the well-being and satisfaction of patients. Results. There were no differences between the groups in terms of demographic characteristics, duration of surgery, and analgesic consumption during the intraoperative period. The severity of postoperative pain was higher (p<0.05) in the control group than in the blockade groups. Both block groups demonstrated lower pain scores at all time points assessed. The latest need for analgesics was in the QLB group. Mean arterial pressure (MAP) values differed only in the first 2 hours after surgery between the CON and TAPB groups (p<0.05). PONV one hour after surgery was more observed in the control group and less in the QLB group (p<0.05). According to the results of a survey conducted on the day after surgery, the number of patients satisfied with the anesthesia and assistance provided in the recovery room in the groups with blockade (TAPB, QLB) was 2.1-5.3% higher (p>0.05). More patients from the QLB group (p<0.05) noted very good and good health, and most patients (p<0.05) from the CON and TAPB group noted satisfactory health. Conclusion. The use of interfascial blocks for postoperative pain relief (TAPB, QLB) after laparoscopic robot-assisted hysterectomy improves the quality of pain relief and the well-being of patients. Benefits of QLB include better pain relief, reduced incidence of PONV, and greater patient satisfaction. TARP has shown equally good results, and this method is easier to perform.